2021
DOI: 10.1007/s00109-021-02121-y
|View full text |Cite
|
Sign up to set email alerts
|

HIF2α regulates the synthesis and release of epinephrine in the adrenal medulla

Abstract: The adrenal gland and its hormones regulate numerous fundamental biological processes; however, the impact of hypoxia signaling on adrenal function remains poorly understood. Here, we reveal that deficiency of HIF (hypoxia inducible factors) prolyl hydroxylase domain protein-2 (PHD2) in the adrenal medulla of mice results in HIF2α-mediated reduction in phenylethanolamine N-methyltransferase (PNMT) expression, and consequent reduction in epinephrine synthesis. Simultaneous loss of PHD2 in renal erythropoietin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…At the physiological level, studies in mice models have shown that HIF2α has prominent functions in the development of the CB and its responsiveness to acute hypoxia [ 6 , 7 , 8 ]. It is also essential for the growth, differentiation, and function of the sympathoadrenal lineage [ 9 , 10 , 11 , 12 ]. However, the roles of HIF1α and HIF2α in HNPGL and PPGL development have been more poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…At the physiological level, studies in mice models have shown that HIF2α has prominent functions in the development of the CB and its responsiveness to acute hypoxia [ 6 , 7 , 8 ]. It is also essential for the growth, differentiation, and function of the sympathoadrenal lineage [ 9 , 10 , 11 , 12 ]. However, the roles of HIF1α and HIF2α in HNPGL and PPGL development have been more poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Increased chromogranin A expression has also been reported in patients with type 1 diabetes [ 77 ] and it correlates with increased plasma catecholamine levels during the early stages of diabetes [ 78 , 79 ]. As HIF-2α regulates expression of catecholamine biosynthetic enzymes in adrenal chromaffin cells [ 80 82 ], we analyzed the expression of HIF-2α in adrenal glands. The levels of HIF-2α protein were highly variable in Hif1aCKO, with undetectable expression in two samples from diabetic and one sample from non-diabetic Hif1aCKO (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report claimed no association of PD‐L1 expression and HIF in PPGL [ 30 ]. However, that study analyzed HIF1α as a pseudohypoxia biomarker that, in contrast to HIF2α, does not distinguish between SDH ‐mutated and SDH ‐wild‐type tumors [ 32 , 40 ].…”
Section: Discussionmentioning
confidence: 99%